USER STUDY ON PURPOSE AND FREQUENCY OF LIBRARY USAGE AMONG J. M. PATEL COLLEGE BHANDARA STUDENTS - Yeole, Mona Shambhau; T. Aagashe, Prince Ajaykumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study focuses on the frequency of student library visits as well as the many reasons they use it. To learn more about the reasons for and usage trends of the library, information was gathered from 446 students. The J.M. Patel College of Arts, Commerce, and Science in Bhandara was founded in 1964. It is situated in an urban area. It’s situated in Maharashtra’s District Bhandara. There are 99 lakh books at the college library. The user walks 100–120 per day. According to the monthly report of college library, taking out books is the most popular activity, whereas getting ready for lectures and passing the time are the least prevalent uses. According to the real needs of students, this analysis attempts to assist academic institutions in optimising library resources and services.